Development of Human-Machine Interface IoT Learning Media Based on Android for Sorting Machines - Prastyo, Adam; Ardiansyah, Mochamad Wildan; Romadhoni, Revianto; Purnomo, Purnomo (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This research seeks to create an Android app that serves as a Human Machine Interface (HMI) learning tool for sorting machines, which will be used in the interface and data communication course in the Industrial Electronics Engineering department at SMKN 1 Rejotangan. The method used is the Research and Development (R&D) model by Borg & Gall, simplified into five stages: analysis, planning, development, product validation, and testing. According to the research results, the analysis stage identified the need for learning media. The HMI design was developed during the planning stage, and during the development stage, the application was created using the Android platform. Product validation results by subject matter experts and design experts show excellent conformity. Product trials with students show that this HMI application is practical and helps students understand IoT concepts easily. In conclusion, this Android-based HMI application is helpful as a learning medium to enhance students' understanding of interfaces and data communication.